2015
DOI: 10.1016/j.neuropsychologia.2014.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating the neural mechanisms of distance and spatial reference frames

Abstract: (2015) 'Dissociating the neural mechanisms of distance and spatial reference frames. ', Neuropsychologia., Further information on publisher's website:https://doi.org/10.1016/j.neuropsychologia. 2014.12.019 Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Neuropsychologia. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be re ected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, studies on the interaction between spatial domains and reference frames have found that individuals show processing precedence for egocentric presentation and near-space processing 4 , 6 , 7 , 22 . For example, Chen and colleagues 4 found that participants preferred egocentric representation, with a faster response in egocentric tasks regardless of near or far space.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, studies on the interaction between spatial domains and reference frames have found that individuals show processing precedence for egocentric presentation and near-space processing 4 , 6 , 7 , 22 . For example, Chen and colleagues 4 found that participants preferred egocentric representation, with a faster response in egocentric tasks regardless of near or far space.…”
Section: Introductionmentioning
confidence: 99%
“…Organized searches can be measured according to their consistency (maintaining the same search pattern), number of intersections (search path crossing over itself), and distances between targets (finding the next target close to the previous one; Ten Brink et al, 2016). Moreover, our visuospatial attention operates to find stimuli in peripersonal (within reach/near-space) and extrapersonal space (out of reach/far-space) and locate them using egocentric (location of objects relative to the body) and allocentric (relative to other objects) reference frames (Lane et al, 2015). The central role visual search plays in everyday life becomes apparent when observing deficits in visuospatial attention after brain injury or changes with healthy aging.…”
Section: Introductionmentioning
confidence: 99%